Probiotics - Cid Rigobelo, Everlon (IntechOpen, 2012)
Over the last few decades the prevalence of studies about probiotics strains has dramatically grown in most regions of the world. Probiotics are specific strains of microorganisms, which when served to human or animals in proper amount, have a beneficial effect, improving health or reducing risk of getting sick and the probiotics are used in production of functional foods and pharmaceutical products. This book provides the maximum of information approaching issues as probiotics in food, health, biotechnological aspects and the use of probiotics in aquaculture for all that need them trying with this to help many people at worldwide.